2017
DOI: 10.1186/s12872-017-0542-1
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension in Cameroon associated with high likelihood of obstructive sleep apnea: a pilot study

Abstract: BackgroundAlthough disordered sleep patterns predispose to hypertension (HTN), little is known on the effect of the latter on sleep patterns in sub-Saharan Africa. This study therefore sought to generate preliminary data on the likelihood (risk) of Obstructive sleep apnea (OSA) in hypertensive patients, with the aid of sleep questionnaires.MethodsThis case–control study, age-and-sex-matched HTN patients with normotensive participants, and compared sleep patterns in either group determined with the aid of the B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
1
3
1
Order By: Relevance
“…The prevalence of high risk of OSAHS we found in the present study using the STOP--BANG questionnaire is as high as previously reported by Sharma et al in 2015, in a study including obese patients admitted in a department of internal medicine [14]. In another study conducted by Njamnshi et al in Cameroon, 60% of patients with hypertension treated as outpatients were found to have a high risk of OSAHS using the Berlin questionnaire [25]. In the present study including patients with several comorbidities, the risk of OSAHS was found to be much higher than that assessed in the general population using the same questionnaire; namely 17.8% in Cameroon [10] or 36.9% in Nigeria [9].…”
Section: Discussionsupporting
confidence: 85%
“…The prevalence of high risk of OSAHS we found in the present study using the STOP--BANG questionnaire is as high as previously reported by Sharma et al in 2015, in a study including obese patients admitted in a department of internal medicine [14]. In another study conducted by Njamnshi et al in Cameroon, 60% of patients with hypertension treated as outpatients were found to have a high risk of OSAHS using the Berlin questionnaire [25]. In the present study including patients with several comorbidities, the risk of OSAHS was found to be much higher than that assessed in the general population using the same questionnaire; namely 17.8% in Cameroon [10] or 36.9% in Nigeria [9].…”
Section: Discussionsupporting
confidence: 85%
“…This association has been described in several studies in epidemiological western studies [ 4 , 5 , 47 ]. More recently in our setting, Njamnshi et al reported 60% of hypertension in patients with HR-OSAS and only 20% in patients with no risk [ 19 ], while we found 75.4% in patients with confirmed SAS. Surprisingly, we found no association between SAS and metabolic comorbidities, and obesity and diabetes were even more frequent in non-MS-SAS than in MS-SAS.…”
Section: Discussioncontrasting
confidence: 59%
“…Balkissou et al found a SDB rate of 28.5% among an adult sample in Cameroon [ 13 ], while Benjafield et al's epidemiological estimation was 36.7% for Cameroon [ 16 ]. Besides those population-based data, hospital-based or clinical studies showed higher rates: 50%-77% for HR-OSAS in Nigeria and Cameroon [ 17 19 ] and 57.7% for SDB in Cameroon [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hypertension is a globally public health problem, and OSAS is one of its modifiable risk factors [ 11 , 12 ]. Some studies found that there was a significantly positive association between hypertension and OSAS [ 13 , 14 ]. The prevalence of OSAS is approximately 30–40% in hypertensive patients [ 15 ].…”
Section: Introductionmentioning
confidence: 99%